Analytic study of the application of the new curricular reform in the basic unit of the military school “Tcrn Lauro Guerrero” in Loja city during the school year 2009– 2010 - Castillo Moreno, Susana María (2011)
THE ANALYTIC STUDY OF THE APPLICATION OF THE NEW CURRICULAR REFORM IN THE BASIC UNIT OF THE “TCRN LAURO GUERRERO” MILITARY HIGH SCHOOL IN LOJA CITY DURING THE SCHOOL YEAR 2009-2010, is a document of analysis. The main method used to develop this work, was the scientific method, which has helped us to find the true about the researched object. We also used some particular methods: analytic, synthetic, inductive, deductive, and materialistic-dialectical; to develop every part of the investigation. The main instrument that was applied to collect information was the survey, directed to a selected sample of teachers, students and parents, which have helped us to check the hypothesis outlined in this investigation, and obtain clear and objective conclusions. Finally, we have outlined our recommendations with the purpose of helping to improve the educational level of the students, having as a reference the limits in which the Curricular Reform is based.